Tell Me More: Promoting compassionate patient care through conversations with medical students - Danielle Qing (The Beryl Institute, 2018)
Tell Me More® (TMM) is a medical student driven project that represents a movement amongst the rising generation of physicians to practice humanistic, patient-centered medicine through a collaborative approach. Students interviewed patients to create individualized posters designed to build rapport and trust between patients and clinicians, remind patients of their special strengths by highlighting their unique interests and qualities, and encourage more personal and compassionate patient-clinician interactions in order to enhance the patient experience. Students asked each patient three questions: 1. “How would your friends describe you?” 2. “What are your strengths?” 3. “What has been most meaningful to you?” and answers were recorded on a large poster, which was displayed prominently in the patient’s room for clinicians and staff to acknowledge. TMM engaged 5 students and 302 patients over 4 hospital settings throughout Northwell Health. Data collection included daily written reflections by students on their experiences, exit interviews with patients to assess the impact of the project on their stay, and staff surveys that addressed provider perception of the program. Descriptive outcomes supported a positive impact on students, patients, staff and clinicians. TMM succeeded in providing a bridge between patients and clinicians and is a cost-effective practice that lends to more personal patient-provider interactions. Bedside posters positively influenced the culture of a hospital organization and reminded providers of the meaning in their work, which literature shows can reduce provider burnout and improve quality of care.